Lockouts in India, 1961-2001 - Shyam Sundar, K.R. (2004)
This article attempts an aggregate and disaggregate quantitative analysis of lockout data in order to comprehensively understand the phenomenon of lockouts in India. While the incidence of lockouts has clearly risen over the years, the extent of increase depends on the statistical measure chosen for analysis. There is a need to improve the data of both the classification and causes of work stoppages to better reflect the realities. - Reproduced.
Keywords: Lockouts - India; Lockouts